Crosstab Analysis Of Tourists Spending Pattern In Yogyakarta - Nining Yuniati (International Journal of Science, Technology & Management, 2023)
This research is a review of the results of a survey of tourist spending data in Yogyakarta conducted by the Yogyakarta Provincial Tourism Office. The aim of is information on the amount of tourist spending and several information related to gateway, frequency of visit, member of trip, length of stay, method of payment, shopping preference, and mode of transportation. The results obtained show that tourist spending in Yogyakarta is still relatively small, amounting to less than 200 thousand IDR per day. The shopping component is accommodation, culinary or gastronomy, and souvenirs. Based on the exit gateway, tourists who leave through the airport have a higher variation in spending compared to other exit gateways. Based on visit frequency, the majority are repeaters with more than 5x visits. Based on member of trip Most visits are with friends. The average length of stay is 1 day or less. The preferred payment method is cash. Shopping preferences are friends' recommendations. The mode of transport that is widely used is the private car.